Nurses’ Perception of Learning Organization Dimensions - Alatawi, Sarah Ruwayi F; Salem, Olfat A; Nazik, Zakari MA (International Journal of Medical and Health Sciences Research, 2022)
Converting the healthcare delivery system into a learning organization is essential for improving health outcomes. As nurses are the forces that implement changes to meet organizational objectives, they are continuously involved in the learning process. This study aims to explain the learning organization dimensions as perceived by Nursing staff in Saudi Arabia. This is a descriptive study that uses a convenience sample of 550 nurses. Data was collected using The Dimensions of the Learning Organization Questionnaire (DLOQ). The questionnaire consists of seven dimensions of learning organization. The DLOQ is based on a six-point Likert scale which was scored from 1-6. The study found the highest perceived dimension was “Embedded Systems.” While the lowest perceived dimension was “Empowerment.” The study concluded that while some dimensions were perceived highly by nurses like embedded systems, some dimensions, like system connections and empowerment, were perceived lowly which indicates areas of weaknesses in the organization.